2022
DOI: 10.31234/osf.io/kgqun
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel free-operant framework enables experimental habit induction in humans

Abstract: Habits are a prominent feature of behavior. Despite substantial research efforts, there are currently no well-established experimental procedures for habit induction in humans. To address this gap, we developed a novel gamified smartphone application for habit induction, free of typical laboratory constraints. We devised a unique real-world free-operant task structure, whereby participants could voluntarily enter the app (24 hours a day, 7 days a week) to win rewards. In a preregistered study we demonstrated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Therefore, we are unable to firmly conclude that the action sequences are habits rather than, for example, goal-directed skills. According to a very recent study, also employing an app to study habitual behavior, the criterion of devaluation resistance was shown to apply to a three-element sequence with less training ( Gera et al, 2022 ). Thus, overtraining of our six-element sequence might also have achieved behavioral autonomy from the goal in addition to behavioral automaticity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we are unable to firmly conclude that the action sequences are habits rather than, for example, goal-directed skills. According to a very recent study, also employing an app to study habitual behavior, the criterion of devaluation resistance was shown to apply to a three-element sequence with less training ( Gera et al, 2022 ). Thus, overtraining of our six-element sequence might also have achieved behavioral autonomy from the goal in addition to behavioral automaticity.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated though that even short overtraining (1 day only) is effective at producing habitual behavior in participants high in affective stress (Pool et al, 2022), confirming previous suggestions for the key role of anxiety and stress on the behavioral expression of habits (Dias-Ferreira et al, 2009;Hartogsveld et al, 2020;Schwabe and Wolf, 2009). Here we have trained a clinical population with moderately high baseline levels of stress and anxiety, with training sessions of a higher order of magnitude than in previous studies (de Wit et al, 2018Wit et al, , 2018Gera et al, 2022) (30 days instead of 3 days). By all accounts our overtraining is valid: to our knowledge the longest overtraining in human studies achieved so far.…”
Section: Implications For the Dual Associative Theory Of Habitual And...mentioning
confidence: 99%
“…Therefore, we are unable to firmly conclude that the action sequences are habits rather than, for example, goal-directed skills. According to a very recent study, also employing an app to study habitual behavior, the criterion of devaluation resistance was shown to apply to a simple 2-element sequence with less training (Gera et al, 2022). Thus, it remains possible that the overtraining of our 6-element sequence might have achieved behavioral autonomy from the goal in addition to behavioral automaticity.…”
Section: Discussionmentioning
confidence: 99%
“…The habit‐based approach to behaviour change has, however, attracted criticism for seemingly failing to realise its potential (Segar, 2022). The persistence of habitual responses even when they no longer serve valued goals, a key characteristic of habit commonly observed among animals in lab‐based studies, does not reliably replicate to humans in real‐world contexts (de Wit et al., 2018; Gera et al., 2023; Linnebank et al., 2018). Commentators have questioned whether complex behaviours can become fully automated (Maddux, 1997).…”
Section: Introductionmentioning
confidence: 99%